PERFORMING IDENTITY THROUGH CREATIVE INDUSTRIES: AUDIO VISUAL MEDIA, DESIGN, FINE ARTS, HANDICRAFTS, MUSIC, AND INDIA’S CULTURAL DIPLOMACY IN THE INTERNATIONAL ARENA - Chandra, Ramesh; Chandel, Jayant; Yadav, Vikash; Ramadevi, V.; Patil, Balkrishna K; Karwande, Vijay Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
India performs and negotiates its cultural identity through a wide spectrum of creative industries, including audio visual techniques and media production, fashion, interior and industrial design, fine arts, handicrafts, and music and performing arts. It argues that these diverse cultural forms function as instruments of soft power, enabling India to project narratives of heritage, innovation, and modernity in the international arena. By analyzing state sponsored initiatives, global festivals, exhibitions, and transnational collaborations, the study highlights how India leverages creative expression to foster dialogue, enhance visibility, and strengthen its global standing. Situating these practices within the broader discourse of international relations, the paper demonstrates that cultural diplomacy is not merely symbolic but a strategic dimension of foreign policy. Ultimately, the research underscores the dynamic role of creative industries in shaping India’s identity as a cultural actor on the world stage.